2006
DOI: 10.1002/humu.9463
|View full text |Cite
|
Sign up to set email alerts
|

A new genetic isolate with a unique phenotype of syndromic oculocutaneous albinism: clinical, molecular, and cellular characteristics

Abstract: An extended, highly consanguineous Israeli Bedouin family with at least 20 individuals exhibiting a unique phenotype of oculocutaneous albinism (OCA) was identified. All known OCA genes were excluded in this family. Electron microscopic analysis of platelets revealed absence of dense bodies, suggesting a diagnosis of Hermansky-Pudlak syndrome (HPS). HPS is a rare autosomal recessive disorder of lysosome-related organelle biogenesis, clinically characterized by OCA and platelet dysfunction, sometimes accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Primer pairs were designed for PCR amplification of each exon and their adjacent intron sequences of HPS human candidate genes (Table 1). Primer sequences are available upon request and have been previously described for HPS1 [49], AP3B1 [25], HPS3 [29], HPS4 [20], HPS5 [30] and HPS6 [32]. Standard PCR amplification procedures [48] were employed.…”
Section: Mutation Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Primer pairs were designed for PCR amplification of each exon and their adjacent intron sequences of HPS human candidate genes (Table 1). Primer sequences are available upon request and have been previously described for HPS1 [49], AP3B1 [25], HPS3 [29], HPS4 [20], HPS5 [30] and HPS6 [32]. Standard PCR amplification procedures [48] were employed.…”
Section: Mutation Analysismentioning
confidence: 99%
“…Therefore, these results suggested that patients 88 and 156 suffer from HPS due to mutations causing BLOC-2 deficiency, and that patients 45, 94 and 128 suffer from HPS due to BLOC-3 deficiency. Based on reported differences in the severity of HPS disease caused by BLOC-2 deficiency (in HPS-3, -5 or -6 [8,11,[29][30][31][32]) or BLOC-3 deficiency (in HPS-1 or -4 [18][19][20][21][22][23]), one would then expect that patients 88 and 156 should suffer from a mild form of HPS and that patients 45, 94 and 128 should be at a higher risk of developing pulmonary fibrosis or GI disease. Unfortunately, only two of these patients (88 and 45) were examined at an age in which the validity of these predictions could begin to be evaluated: at the time of their last evaluation at the NIH Clinical Center, patients 88 (age 40 years), 94 (age 2 years), 128 (age 2 years) and 156 (age 19 years) had no signs of interstitial lung disease of GI disease, while patient 45 (age 35 years) presented with a history of GI disease but no interstitial lung disease.…”
Section: Analysis Of Samples From Hps Patients Of Unknown Genetic Lesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a series of recent observations has brought this idea into question. First, deficiencies in each BLOC in human and mouse fibroblasts, which normally express all BLOC subunits but lack LROs, resulted in phenotypes that, albeit mild, revealed that these complexes can play physiological roles in the 'conventional' endosomal-lysosomal system (17)(18)(19)(20)(21)(22). Second, characterization of acidocalcisomes, which are specialized organelles found in a wide variety of non-metazoan eukaryotes, revealed several properties consistent with their classification as LROs (23,24), thus casting doubt on the assumption that LROs would be unique to metazoans.…”
mentioning
confidence: 99%